Locus of Control on Pro-Environmental Behavior: The Role of Attitude toward Pro-Environmental Behavior - Zulkifli Musannip Efendi Siregar; Rina Masruroh; Abd. Rasyid Syamsuri; R.Indra Kusuma Jaya; Dini Hariyati Adam (Universitas Pendidikan Ganesha, 2022)
Students’ behavior related to environmental protection and conservation is very important to discuss. Action pro-environmental every people, through the change of daily habits and behavior, is needed to decrease environmental problems and promote a clean, healthy, and unpolluted environment. This study aims to analyze the locus of control’s effect and attitude toward pro-environmental behaviours’ effect on the students’ pro-environmental behavior. This study uses an online survey method. A total of 386 respondents were collected. Therefore, the sample in the study amounted to 386 respondents. We used quantitative and structural equation modeling methods to examine the hypotheses. The data were processed by Amos software version 23. This study found that locus of control affects the attitude toward pro-environmental behavior. The locus of control and attitude toward pro-environmental behavior also positively affect students’ pro-environmental behavior. We invented that attitudes toward pro-environmental behavior did not mediate the effect of students’ locus of control on the pro-environmental behaviours of the students. The suggestion to improving the students’ locus of control and attitude related to the environment to gain and enhance the students’ pro-environmental behavior. The originality or value of this study gives a new insight into understanding the interaction between students’ locus of control and attitude toward the environmental behavior of the students in Indonesia.